Challenging the status of the National Council of the Judiciary - Drożdżejko, Zygmunt (Finding a way out of Poland’s rule-of-law crisis: Possible courses of action and reform, 2026)
Since December 13, 2023, Donald Tusk's government has consistently refused to recognize the legitimacy of the National Council of the Judiciary (KRS), arguing that the procedure by which its judicial members are selected is incompatible with both domestic and international law. This position is maintained despite the fact that the Constitutional Tribunal has explicitly upheld the constitutionality of the current selection model under the Polish Constitution, and the Court of Justice of the European Union has never directly challenged the manner in which judges are appointed to the KRS. The practical consequences of this stance have been severe. The Minister of Justice abandoned his statutory duty to announce vacancies on the benches of common courts, resulting in 678 unfilled judicial positions as of August 2025. At the same time, judges who had reached the mandatory retirement age of 65 continued to adjudicate without the required KRS consent, while the ministry effectively usurped the Council's authority. The author also documents a broader pattern of unlawful conduct: the removal of court presidents, the introduction of unconstitutional regulations enabling the reassignment of judges from specific cases, and the public questioning of the status of judges appointed after 2017. Particularly troubling is the fact that part of the judiciary itself joined in undermining the status of fellow judges — in extreme cases going so far as to overturn rulings solely on the grounds that a judge appointed after 2017 had sat on the panel. The chapter concludes with a set of remedial measures and long-term reform proposals. In the short term, the government should immediately cease all actions that call into question the status of judges, announce available judicial vacancies, and notify judges who have reached retirement age of their transition to senior status. Disciplinary proceedings should be initiated against those who continued to serve past the mandatory retirement age, as well as against court presidents who permitted them to sit on panels. Looking further ahead, the author notes that while there is no legal imperative to alter the current system for selecting KRS members, certain adjustments could help ease political tensions surrounding the issue. The author also advocates transferring the authority to announce judicial vacancies from the Minister of Justice to the President of the Republic of Poland, which would reduce the executive branch's ability to obstruct the judicial appointment process.